Recognition and endodontic management of maxillary first premolars with two roots and three canals. Bilaterality case report - Molina Quispe, Jairo Jhoel (2023)
The ability to recognize the anatomical variations of the root canal system is crucial before starting endodontic treatment, no less important is being able to carry out these treatments based on current scientific evidence. The premolars are the dental pieces with the greatest complexity in their internal anatomy and the ones that appear in the highest percentage compared to other teeth, if a piece presents accessory anatomy, it is highly probable that the contralateral piece presents the same internal anatomy, to this it is known as symmetrical bilaterality, therefore the radiographic images must be executed with proximal and orthoradial projections in order to approximate the 3D shape that these anatomies present and minimize procedural errors. The use of magnification is essential to be able to address the entire root canal system and perform an adequate endodontic treatment. This case report presents the approach to 2 maxillary first premolars from the same patient with 3-canal anatomy, presenting bilateral symmetry.